2019
DOI: 10.29244/avi.7.2.1-8
|View full text |Cite
|
Sign up to set email alerts
|

Transmisi Strain Wuchereria bancrofti Periodik Nokturnal oleh Culex quinquefasciatus di Kota Pekalongan

Abstract: Wuchereria bancrofti dikenal sebagai penyebab filariasis limfatik di Kota Pekalongan. Kegiatan ini dilakukan untuk mencari upaya dalam pengendalian penularan filariasis limfatik yang lebih efektif dan efisien. Tujuan penelitian untuk mendiskripsikan perilaku mikrofilaria Wuchereria bancrofti yang ditularkan oleh Culex quinquefasciatus. Uji periodisitas dilakukan pada enam orang relawan yang positif mengandung mikrofilaria hasil survei darah. Pengambilan darah dilakukan setiap dua jam sekali selama 24 jam (12 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…This mosquito was believed as a main vector for W. bancrofti in the urban areas. 4,17,18 It can be explain that in these areas have potentially of filariasis transmission due to the positive results in microscopic examination and the mf density in the non-elephantiasis patient, It could be noted that these areas have potentialities of filariasis transmission due to the positive results of microscopic examination and the mf density in the non-elephantiasis patients. It is possible that there are quite high sufferers and vectors, although the findings in this study were low.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This mosquito was believed as a main vector for W. bancrofti in the urban areas. 4,17,18 It can be explain that in these areas have potentially of filariasis transmission due to the positive results in microscopic examination and the mf density in the non-elephantiasis patient, It could be noted that these areas have potentialities of filariasis transmission due to the positive results of microscopic examination and the mf density in the non-elephantiasis patients. It is possible that there are quite high sufferers and vectors, although the findings in this study were low.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti have not yet confirmed as a vector of filariasis in Central Java; however, a Ramadhani's study on periodicity of W. bancrofti microfilariae found that 14% of microfilariae were still circulating in the peripheral blood at 6 am. 4 On the other hand, in the morning the Aedes mosquito has started to increase in density. These two phenomena allow transmission of filariasis by Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The urban filariasis vector is Culex quinquefasciatus mosquito, while the rural includes Anopheles, Culex, and Aedes mosquitoes. 4 In Central Java, there were 439 chronic cases of filariasis in 2018 and it was ranked 6 th as the province with the highest number of filariasis cases in Indonesia. 1 Efforts to eliminate filariasis are in line with the strategy formulated by the World Health Organization, which is based on large-scale treatment activities to suppress the spread of the disease and reduce the disability impact caused by filariasis.…”
Section: Introductionmentioning
confidence: 99%